O Estado constitucional da era Vargas: uma abordagem à luz do pensamento social brasileiro dos anos 30 - Silva, Fernanda Xavier da (2006)
Starting from the historical context of thirties years occasion of breakdown of the international liberalism and the Brazilian political system we analyzed the constitutions of 1934 and 1937, seeking for an answer to the following question: how two so different states systems could subsist under the same historical context? We tried to understand in which dimension these constitutionals texts were under the influences of the political-and-cultural ambient, and also in which degree they was taken by then the ideologies under discussions. It is important to keep in mind that both Constitutions shared similar rudiments and none of them fit under the usual theoretical label. As an effort to provide this answer, we studied the Brazilian social thought during the thirties years, and face it with the main ideas that figure in these constitutionals letters. As a result, we tried to take out the essentials aspects of these letters, taking them not as just simples juridical texts, but as legislations produced under the influences of a specific political-and-cultural ambient.